Analisis Re-Branding Logo Halal Indonesia dalam Perspektif Teori Gestalt: Penelitian - Maysya Tri Putri; Daniel Handoko (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Ministry of Religion of the Republic of Indonesia through its official website and Instagram account in March 2022 established and released the